MyUfm song online voting system / Nor Amalina Shaaffiee - Shaaffiee, Nor Amalina (2013)
Radio Kampus UiTM Terengganu, MyUfm is the first campus academic radio station on the East Coast located at Dungun, Terengganu and owned by Universiti Teknologi MARA (Terengganu). It was established in 2005. In 2010, MyUfm introduced a program slot called “MyUfm Carta 21 ” which needs an automated song voting in order to ease music manager to organize them. Currently, the voting process is done manually. There is no systematic way to determine the latest popular song. For that reasons, the project entitled “MyUfm Song Online Voting System ” is developed to ease listeners, voters, crews, music manager, deejay, producer, and even individual in voting and managing the “MyUfm Carta 21”. This project developed using Waterfall Model that went through each phases which knowledge acquisition, system requirement, system design, and system development. MyUfm Song Online Voting System enables voter to vote and to see the changes of chart eveiy week. Besides that, administrator can add song and singer as well as updating and deleting the records information. Administrator also can view the voting records. At the end, it is found out that the system is effective to use based on positive feedbacks from respondents. This system should be expanded more by including “add more” function in adding song so that administrator did not need to repeat the same process when they have many songs to add at one time.